The impact of overtime duration variations on labor productivity in apartment construction projects: A study on engineering and disaster management in the construction sector - Mirnayani; Paradiba, Hafisa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Construction projects, especially apartment buildings, often face challenges such as resource limitations, unpredictable weather, and schedule delays, which lead to increased costs and reduced productivity. Overtime is a commonly adopted strategy to address these issues; however, its effect on labor productivity is complex. Methods: This study investigates the impact of varying overtime durations (1, 2, and 3 hours) on labor productivity and Labour Utilization Rate (LUR) for three critical tasks: rebar installation, concrete casting, and formwork installation in the Sky House Alam Sutera project. The Productivity Rating method and LUR analysis were used to evaluate normal productivity and productivity during overtime, with data collected through direct observation, interviews, and project documentation analysis. Findings: The results reveal that while overtime increases daily output, it also reduces productivity per hour as work hours extend. Rebar installation exhibited the most significant decline in productivity, from 493.529 kg/hour during regular hours to 345.470 kg/hour with 3 hours of overtime. Correspondingly, the LUR improved with overtime, with rebar installation increasing from 68% under normal conditions to 72% with 3 hours of overtime. Similarly, the cost of labor increased by 9%–23% due to overtime, depending on the task and duration. Conclusion: The findings suggest that the optimal overtime duration is 1 hour, balancing productivity gains, cost efficiency, and LUR improvements, while prolonged overtime may lead to diminishing returns due to worker fatigue. This study provides insights into managing overtime in construction projects, emphasizing the importance of controlling overtime durations to achieve project objectives efficiently. Novelty/Originality of this article: This study offers an original perspective by examining the impact of varying overtime durations on both labor productivity and Labor Utilization Rate (LUR) in the context of construction projects, using a detailed analysis of three critical tasks.